2016
DOI: 10.1208/s12248-015-9853-2
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Bayesian Mathematical Model to Predict the Impact of Immunogenicity on Pharmacokinetics of Therapeutic Proteins

Abstract: Abstract. The impact of an anti-drug antibody (ADA) response on pharmacokinetic (PK) of a therapeutic protein (TP) requires an in-depth understanding of both PK parameters and ADA characteristics. The ADA and PK bioanalytical assays have technical limitations due to high circulating levels of TP and ADA, respectively, hence, significantly hindering the interpretation of this assessment. The goal of this study was to develop a population-based modeling and simulation approach that can identify a more relevant P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Immune response varies from patient to patient and also within patients, as the concentration and nature (isotype, affinity) of the ADA distribution change with time and with continued drug dosing [269]. Mathematical models have shown utility in their ability to characterize ADA responses following different doses, and to develop relationships between drug exposure and the impact of ADA on drug clearance [287,288]. In clinic, increasing the mAb dose, co-administration of immunosupressants [289][290][291] and switching to a different mAb [292] are considered as strategies to overcome immunogenicity and have shown moderate benefit.…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%
“…Immune response varies from patient to patient and also within patients, as the concentration and nature (isotype, affinity) of the ADA distribution change with time and with continued drug dosing [269]. Mathematical models have shown utility in their ability to characterize ADA responses following different doses, and to develop relationships between drug exposure and the impact of ADA on drug clearance [287,288]. In clinic, increasing the mAb dose, co-administration of immunosupressants [289][290][291] and switching to a different mAb [292] are considered as strategies to overcome immunogenicity and have shown moderate benefit.…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%
“…Empirical models with time-varying PK parameters have been used to study the impact of immunogenicity on PK of TPs. For example, a parameter termed change in clearance time (𝛼) was included in a two-compartment TMDD model, which allows the linear clearance to suddenly change at time 𝛼, presumably due to ADA formation (Kathman et al, 2016). It was found that the derived 𝛼 can be much earlier than the time when ADA is detected in bioassays, and thus is helpful in identifying falsenegative subjects.…”
Section: Immunogenicitymentioning
confidence: 99%
“…ADA PRED,T,ijk = ADA OBS,BL,ik + ADA PRED,M,ijk + ADA PRED,G,ijk (4) log 2 (ADA T,ijk ) = log 2 (ADA PRED,T,ijk ) ⋅ (1 + prop,ijk ) + add,ijk (5) P i = TVP i ⋅ exp( P,i ) (6) η P,i_Box−Cox = ((e η P,i ) γ − 1) γ (7) TVP…”
Section: Prediction Of Ada Incidencementioning
confidence: 99%
“…Modeling-based approaches have been reported to assess the impact of ADAs on pharmacokinetics/pharmacodynamics (PKs/ PDs) and efficacy. [4][5][6] Chen et al 4 reported a mathematical PK/ ADA model to quantify the impact of immunogenicity on protein drug clearance based on concentration data from animal studies. This work described scenarios on the potential time course and dynamics of the development of ADA.…”
mentioning
confidence: 99%